2000
DOI: 10.1046/j.1525-1470.2000.017005391.x
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Tragus: Report of Two Cases and Review of the Literature

Abstract: Accessory tragus is a fairly common congenital malformation of the external ear. In the vast majority of cases it is an isolated developmental defect not associated with other abnormalities. However, the remote possibility exists that it could be associated with other abnormalities of the first and second branchial arch. Accessory tragus is a consistent feature of the oculoauriculovertebral syndrome (Goldenhar syndrome). When correctly identified, surgical excision of accessory tragus is quite simple and rarel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 23 publications
0
27
0
2
Order By: Relevance
“…It may hence be concluded that whereas external lesions are a consistent feature of the Goldenhar syndrome, the opposite is not true (1,3,(7)(8)(9). The cases we are reporting did not have any indication of Goldenhar syndrome.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…It may hence be concluded that whereas external lesions are a consistent feature of the Goldenhar syndrome, the opposite is not true (1,3,(7)(8)(9). The cases we are reporting did not have any indication of Goldenhar syndrome.…”
Section: Discussionmentioning
confidence: 60%
“…The anomalous differentiation and consequent heterotopic tissue by inference should originate from immature pluripotent cells. The stimuli for the process remains unknown but it should be mostly a stochastic event given the lack of family history in most of these cases and also the fact that most of them are unilateral (7,8,9). …”
Section: Discussionmentioning
confidence: 99%
“…Pyogenic granuloma, which is a common, benign vascular lesion, could be ruled out by characteristic histological features, showing lobular aggregates of capillaries and venules lines by plump endothelial cells with fibrous septa (3). Accessory tragus can be differentiated, in that it showed a central plate of elastic cartilage, histologically, and is usually evident at birth (4). The most common therapeutic options are surgical excision and pulsed dye laser.…”
Section: Diagnosis: Angiolymphoid Hyperplasia With Eosinophiliamentioning
confidence: 99%
“…Tragus accessoires formés d'un fragment de cartilage élastique saillant, recouvert de peau (lésion dite d'« enchondrome cutané »), éventuellement dans le cadre d'un syndrome branchio-otorénal [5].…”
Section: Tragus Accessoiresunclassified